Characterization of Biofilm Formation by Exiguobacterium Strains in Response to Arsenic Exposure - Melo-Hurtado, F (American Society for Microbiology, 2023)
The Salar de Huasco (SH) salt lake in northern Chile is an extreme environment characterized by high atmospheric pressure, UV radiation, salinity, variable temperatures, and the presence of heavy metals, including arsenic. Exiguobacterium bacteria have adapted to thrive in these challenging conditions and possess various resistance mechanisms, including biofilm formation, redox reactions, methylation, and altered respiration. In this study, Exiguobacterium strains isolated from the SH were assessed for their capacity to form biofilms in the presence of arsenic, a metalloid that exists in different oxidation states, in order to understand their resistance mechanisms to this heavy metal. The minimum inhibitory concentration (MIC) of each strain against different concentrations of arsenic [III] and [V], biofilm formation using crystal violet staining, and the expression of genes related to biofilm formation were evaluated. The structure of the biofilms was characterized using scanning electron microscopy (SEM) and atomic force microscopy (AFM). Furthermore, the extracellular polymeric substances (EPS) produced during biofilm formation were purified, quantified, and their composition determined. The results showed that the tested Exiguobacterium strains exhibit a significant ability to form biofilms when exposed to arsenic. This biofilm contributes to their arsenic resistance, shedding light on the underlying mechanisms. These findings enhanced our understanding of the biofilm formation process, its role in arsenic resistance, and the adaptive strategies employed by bacteria in extreme environments. This study also contributes to the field of microbial resistance mechanisms that have implications for environmental and biotechnological applications. Copyright © 2023 Pavez et al. This is an open-access rticle distributed under the terms of the Creative Commons Attribution 4.0 International license.